Democratization of Access to Justice through SaaS Platforms: Digital Models for Reducing Economic Barriers in the American Legal System - Reis, Renato de Carvalho dos (Revista ft, 2026)
Access to justice in the United States remains structurally constrained by high legal costs, procedural complexity, and unequal distribution of legal services. The emergence of Software-as-a-Service (SaaS) legal platforms introduces a scalable digital model capable of reducing transactional costs and expanding procedural accessibility. This article analyzes how SaaS architectures—characterized by multi-tenancy, standardized workflows, automation, and subscription-based delivery—reconfigure legal service provision and mitigate economic barriers within the American legal system. Drawing from contemporary scholarship on digital transformation of justice, online courts, legal innovation ecosystems, and socio-legal implications of artificial intelligence, the study examines both the structural opportunities and governance risks associated with “Justice as a Service” models. The analysis demonstrates that SaaS-based legal infrastructures can contribute to substantive access to justice when supported by institutional adaptation, regulatory safeguards, and digital inclusion policies.